Factors affecting Chinese short-term international students’ cross-cultural adaptation in psychology, learning, and life - Zhang H; Li M (Hindawi)
Although Chinese international students’ cross-cultural adaptation has achieved intense research, factors in developing Chinese SISs’ cross-cultural adaptation remain under-researched. This study examined the factors through a survey of Chinese SISs’ transitional adaptation in psychology, life, and learning. Mixed-method research was conducted: a survey of 155 SISs from a top Chinese university undertaking study across 16 countries and in-depth interviews with 15 SISs. Results indicate that knowledge of the host country and university, language proficiency, sense of participation, and engagement are the crucial factors in developing Chinese SISs’ cross-cultural adaptation. These factors reveal significant correlations with the students’ adaptive performances in psychology, life, and learning. However, the factor of duration indicates no significant correlation with students’ cross-cultural adaptation, which demonstrates an inconsistency with the previous studies. The findings of this study highlight the need for developing Chinese SISs’ sense of engagement, enhancing the language training, and building up the knowledge of the host cultures previous to the study abroad.
Keywords: International student; Cross-cultural adaptation; Culture learning; Cross-cultural competence; interlinguistic proficiency; 0102 Applied Mathematics